2016
DOI: 10.1017/s204579601600041x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the Time to Change programme in England as predictor of mental health service users' stigma coping strategies

Abstract: Aims. In the field of stigma research, an area of interest is the coping strategies that mental health service users can use in response to discriminatory experiences. As a part of the evaluation of the Time to Change (TTC) anti-stigma programme, the Viewpoint telephone survey was run annually in order to assess service users' reported levels of discrimination and selected coping strategies. The study aim is to test the extent to which experience of TTC programme is a positive predictor of selected coping stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
(71 reference statements)
1
7
0
1
Order By: Relevance
“…In particular, Abiri et al [32] reported that people with greater insight of the mental health stigma could find it more difficult to limit their impact. It could be that anti-stigma programmes are useful tool for improving positive coping strategies such as challenging and educating others [27], whereas the reduction of the levels of self-stigma might require more specialized psychosocial interventions [32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, Abiri et al [32] reported that people with greater insight of the mental health stigma could find it more difficult to limit their impact. It could be that anti-stigma programmes are useful tool for improving positive coping strategies such as challenging and educating others [27], whereas the reduction of the levels of self-stigma might require more specialized psychosocial interventions [32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The overall consequence of discrimination is the reduction in achieving personal recovery, through the achievement of personal life goals, such as having a satisfying job or a supportive relationship [16][17][18][19][20][21]. As part of the programme evaluation, a series of telephone interviews, called the Viewpoint Survey, was conducted annually between 2008 and 2014, with the primary objective of measuring discrimination experienced by service users [6,24,27]. Consistent with the improvements in stigma related knowledge, attitudes and intended behaviour observed among the general public since 2009, these surveys showed an overall fall in the 4 experience of discrimination between 2008-14 and that fewer respondents stopped themselves from starting a relationship in 2014 compared to 2013 [6], however there was no clear pattern of change in terms of this or other responses to anticipated discrimination [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…La reducción del estigma se ha configurado como un objetivo relevante dentro de las políticas sanitarias de salud mental y se han planteado intervenciones específicas para actuar sobre el mismo. De manera general encontramos tres tipos de programas: por un lado, los que están diseñados como estrategias globales con varios contextos de actuación y mayor alcance poblacional como por ejemplo "Beyonblue" en Australia; (Corrigan, Powell y Al-Khouja, 2015) ,"Time to Change" en Reino Unido (González-Sanguino, Potts, Milenova, y Henderson, 2019;Sampogna et al, 2017) o "Opening Minds" en Canadá (Stuart et al, 2014;Szeto, Dobson, Luong, Krupa y Kirsh, 2019); por otro, los destinados a grupos específicos (adolescentes, estudiantes universitarios, profesionales de la salud, empleadores etc.) (Deb et al, 2019;Harris et al, 2019;Heim et al, 2019;Sugumar, Fleming y Ogden, 2019) y finalmente los programas individualizados para disminuir el autoestigma (Setti et al, 2019;Yanos, Lucksted, Drapalski, Roe y Lysaker, 2015).…”
Section: Introductionunclassified